Detection of Ecological Thresholds and Selection of Indicator Taxa for Epibenthic Communities Exposed to Multiple Pressures - Isabel, Laurie; Beauchesne, David; McKindsey, Chris; Archambault, Philippe (Frontiers in Marine Science, 2021)
The estuary and the Gulf of St. Lawrence in eastern Canada form a vast inland sea facing a myriad of anthropogenic driven pressures. Facing potential repercussions on benthic communities, it is now necessary to quantify the impact of these pressures and develop management tools to detect their effects. The aims of this study are to analyse the distributional patterns of epibenthic communities and to quantify the impact of important pressures on these communities in the estuary and the Gulf of St. Lawrence, in order to select indicator taxa. Epibenthic communities were sampled at 1314 sites covering the estuary and the Gulf of St. Lawrence between 2011 and 2018. Cluster analyses revealed the presence of six distinct epibenthic communities that seem strongly influenced by oxygen concentrations. Threshold analyses confirm oxygen as an important predictor of epibenthic community composition and distribution. A major oxygen threshold is observed around 50-100 μmol O2 L-1, resulting in a shift of community type. At these concentrations and below, opportunistic taxa dominate the community while sensitive taxa are absent or present in very low abundance. Biomass of the latter only starts to increase when oxygen concentrations reach 150 μmol O2 L-1. The species Actinostola callosa, Actinauge cristata, Ctenodiscus crispatus, and Brisaster fragilis were identified as good indicators for detecting this threshold impact on the epibenthic communities. This study provides threshold-based indicator species that help to establish and monitor the ecological state of epibenthic communities in a marine ecosystem exposed to multiple pressures.